Influence of X-chromosome markers on reproductive traits of beef cattle - Carvalho, Caio Victor Damasceno; Hermisdorff, Isis da Costa; Souza, Isadora Saraiva; Junqueira, Gleb Strauss Borges; Magalhães, Ana Fabricia Braga [UNESP]; Fonseca, Larissa Fernanda Simielli [UNESP]; de Albuquerque, Lucia Galvão [UNESP]; Tonhati, Humberto [UNESP]; Carvalheiro, Roberto [UNESP]; de Camargo, Gregório Miguel Ferreira; Costa, Raphael Bermal (Elsevier, 2019)
Sex chromosomes are generally excluded from genomic analyses, although X chromosome is the second largest chromosome and harbors many genes. The objective of this study was to evaluate the effect of X chromosome by identifying its regions associated with reproductive traits in Nelore cows through a genome-wide association and by estimating its linkage disequilibrium. Phenotypic data of 76,845 and 76,700 animals were used for pregnancy at 16 months and age at first calving, respectively, as well as genotypic data of 1,999 females. Linkage disequilibrium was estimated for X chromosome and for autosomes 1 and 2, due to similar size of chromosomes. Single-step method was used for association analysis and some genes with known role in reproduction were reported for both traits, such as KLHL4 which is associated with development of the female reproductive system, and PCDH11X which is associated with the onset of primary ovarian insufficiency. Moreover, some genes were associated with both traits, indicating a pleiotropic effect. However, contribution of the windows in X-chromosome is very small when compared to autosomes: an unexpected fact. The results revealed higher linkage disequilibrium on the X chromosome (0.2248 ± 0.17) compared to the other chromosomes (0.1965 ± 0.14 and 0.1967 ± 0.14 for autosomes 1 and 2, respectively), indicating low recombination rates.
Keywords: Bos taurus indicus; Fertility; Heifers; Linkage desiquilibrium; Reproduction; SNP